20th AIAA/CEAS Aeroacoustics Conference 2014
DOI: 10.2514/6.2014-2474
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Jet Noise Reduction by Nozzle Fluidic Inserts with Simulated Forward Flight

Abstract: The noise produced by supersonic, high temperature jets that exhaust from military aircraft is becoming more of a disturbance. Methods to reduce the noise produced from these jets in a realistic full-scale environment is difficult. This study describes the development and analysis of fluidic inserts for supersonic jet noise suppression. Distributed blowing within the divergent section of the military-style convergent divergent nozzle alters the shock structure of the jet in addition to creating streamwise vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The microphones used are 1/8 in (3.2 mm) pressure field microphones type 40DP from GRAS. More details on the data acquisition and processing, including all spectral corrections to obtain the presented lossless acoustic spectra can be found in prior publications, (see Kuo et al 6 and Powers et al 11 ).…”
Section: B Experimental Approachmentioning
confidence: 99%
“…The microphones used are 1/8 in (3.2 mm) pressure field microphones type 40DP from GRAS. More details on the data acquisition and processing, including all spectral corrections to obtain the presented lossless acoustic spectra can be found in prior publications, (see Kuo et al 6 and Powers et al 11 ).…”
Section: B Experimental Approachmentioning
confidence: 99%
“…With rapid prototyping, a few nozzles are built at a time, and then the injection pressure is varied, rather than having a large nozzle design matrix. For the purposes of this study, results from only fluidic insert configurations (including hole locations, diameters, and flow-rates) that have been shown to be effective with free jets [10] will be shown.…”
Section: Fluidic Insert Nozzlesmentioning
confidence: 99%
“…The research reported in this paper describes further development made to an approach described in earlier publications [2,[9][10][11], on nozzles with hardwalled corrugations replaced by fluidic insert corrugations. This is achieved by carefully distributed blowing in the divergent section of the nozzle.…”
Section: Introductionmentioning
confidence: 95%
“…It is a variable area ratio nozzle capable of adjusting its throat to exit area ratio based on the flight regime. This ratio is chosen as 1.295 to match previous experiments [11][12][13][14]. This is typical of takeoff conditions and corresponds to a design Mach number (M d ) of 1.65.…”
Section: Description Of Nozzle Variantsmentioning
confidence: 99%